A condição docente no olhar de três gerações de professores formadores - Chenet, Neoclesia (2007)
This research was presented to the Post Graduation Program in Education, specifically to the Master Degree level, in the Centro de Educação (Center of Education) at UFSM (Federal University of Santa Maria), for the line of research on Formation, Knowing and Professional Development. The participation in projects of study during my graduation course called my interest to surveys about professors life histories, involving their forming processes. In this sense, the searching project arose focusing on the study about life trajectory of forming professors belonging to academic spaces and who promotes generations of teachers. From the studies that state generation as a group of people who lived in specific period of time and place, it was used the concept of teaching academic generation which includes a group of professors who inserted themselves in the space of professional performance in the Higher Education. The teaching academic generation means the period of time (decade) in which the educator started the professional performance in the Higher Education, bringing the continuities and discontinuities faced in his formation. The decades of 70, 80 and 90 s correspond to the periods of their entrance in the academic teaching in the Center of Education of the Federal University of Santa Maria. My question of research refers to the representations that the academic professors of different generations have constructed in relation to the formation, the professors social places and the conditions of work in different forming places and times, marking the teaching condition, understood as the conditions which give configurations to the professor profession. The objectives I have tried to know were the forming processes of professors who lived in different time and place, as well as the representations that the three generations have build up in relation to the professors social place and to the transformations of the work conditions. Hence, it was chosen the oral narrative making use of semi-structured interview as an instrument to the production of data. The individuals of the research are three professors of the Center of Education who have had their entrance at UFSM during the above mentioned periods. The professors life history, that passed by different epochs and lived different historical periods, bring to this context the uncommon teaching experiences to the current social, political, economical and cultural moments in which were developed their formation. Collaborator s narratives make evident the structures of social institutions. It was known the culture that was relevant in each forming epoch and period of performance to give base in facts which produced these individuals who were referred to, the framed knows, the imaginary representations and the spaces of formation. Belonging to forming and knowledge production spaces, the professors generate a culture related to that period and that produced impressions in their lives and to later generations. The dialogue with academic generations makes evident the distinct experiences produced in the inter-relations, as well the knowledge, the singularities and the changes perceived by the subjects in the space of academic teaching and in their forming trajectory. The imaginary representations that these individuals, professors of different generations build up in relation to the professor subject and his academic condition makes possible the comprehension of the academic teaching constituted process in their point of view and it was evidenced a body of knowing in relation to distinct historical periods.